Wireless Semi-Automatic Delivery Robot Using IoT and Machine Learning - S. Usha,Aman Ulla,Akash PR (International Journal of Advanced Science and Technology, 2020)
Technology and innovation creativity go beyond boundaries and transform the way world conducts business. Today, we are used to everything online and right at our fingertips for easy access. It is possible to receive a package less than two hour after placing order, depending on the delivery location, A future in which a robot pushes you from one location  to other location or you get a delivery from a wireless unmanned vehicle. For trucks that are not very far back, Independent cars are already a reality. The days you typed out directions from your desktop before you left the house are long gone. Today almost everyone is using Global Positioning system, whether it's built-in on their cars or cell phones. Throughout the years, the reliability of these tools has increased dramatically, not only helping angry, missing drivers but also enhancing the supply chain. The advanced precision of GPS makes it possible to raise reproductivity and satisfaction of customer.